A fully biodegradable macromolecular compatibilizer, preparation method and application thereof
By developing a fully biodegradable macromolecular compatibilizer, using its compatibility improvement in biodegradable polymer materials and inorganic fillers, the problem of difficult degradation of traditional polymer materials and high cost of biodegradable materials has been solved, and the preparation of high-performance and low-cost fully biodegradable composite polymer materials has been achieved.
Patent Information
- Application Number
- CN202211640646.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-12-20
AI Technical Summary
Traditional polymer materials are difficult to degrade, resulting in environmental pollution, and biodegradable polymer materials have limitations in terms of cost and degradation speed, which affects their large-scale promotion.
A fully biodegradable macromolecular compatibilizer is developed to improve the compatibility of polymers and inorganic fillers and improve the thermal and mechanical properties of the materials through carbon dioxide-based polymer materials containing carbonate bonds and ether bond structural segments and siloxane side chains.
The compatibility of biodegradable polymer materials and inorganic fillers is significantly improved, the thermal and mechanical properties of the materials are improved, the cost of material preparation is reduced, and good performance is maintained at high filler ratios.
Smart Images

Figure CN115819746B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biodegradable polymer composite material capacity expansion, and in particular to a preparation method and application of a fully biodegradable macromolecular capacity expander. Background Art
[0002] The rapid development of polymer material synthesis technology has provided humans with a large number of new materials that meet the needs of people in daily life, production and construction. At present, polymer materials and their products have become an indispensable part of our production and life. However, while polymer materials bring us great convenience, they also bring many environmental problems. Most traditional polymer materials represented by polyolefins are difficult to degrade. The large-scale disordered use has caused serious white pollution, which in turn has led to soil pollution and marine pollution, seriously threatening the safety of the natural environment on which humans and organisms depend for survival. In particular, in recent years, with the rapid development of industries such as express delivery and takeaway services, the consumption of disposable plastic packaging materials has increased rapidly, causing tremendous pressure on our environment. The development of degradable polymer materials and their products has become a social consensus.
[0003] Biodegradable polymer materials refer to a type of polymer materials that can be decomposed by microorganisms after use and eventually degrade into water and carbon dioxide. Therefore, plastic products made from them as raw materials will gradually degrade in the soil after use, without causing a large amount of accumulation, and can avoid pollution to the soil and the surrounding environment. According to different sources, biodegradable polymer materials are divided into natural degradable polymer plastics, such as starch, cellulose, chitin, etc. The other type is the synthetic biodegradable polymer materials that have developed rapidly in recent years, including PLA, PBAT, PPC and polyhydroxyalkanoate (PHA). These two major types of materials have their own advantages and disadvantages. Natural polymer materials come from renewable earth resources, are abundant in sources, low in price, and can be quickly degraded after use, with little pressure on the environment. However, the structure of this type of material is unclear, and the processing and mechanical properties are poor. The excessively fast degradation rate has also become a bottleneck restricting its use. Synthetic degradable polymer materials, because the parameters such as structure and molecular weight are controllable, and the processing and mechanical properties are significantly better than natural polymer materials. But the problem is that the high cost and the slow degradation rate of some products have become the key issues restricting their large-scale promotion and application.
[0004] Calcium carbonate is an important inorganic chemical product, which is widely used in rubber, plastic, medicine, cosmetics, food and other industries. Calcium carbonate is one of the important fillers of polymer materials. Because it has a large number of polar hydroxyl groups on its surface, it has high surface energy, strong adsorption, and easy aggregation between particles. Secondly, the surface of calcium carbonate is hydrophilic and oleophobic. After being directly blended with PPC, it is easy to form aggregates inside, causing internal defects of the polymer and deteriorating thermodynamic properties. In order to improve the filling performance of calcium carbonate in PPC, it is necessary to use effective processes and surface modification methods to modify the surface of calcium carbonate.
[0005] In response to the above problems, the preparation of high-performance and low-cost fully biodegradable polymer composites through biodegradable polymers and inorganic fillers is an important direction in the industry. This route can make full use of the advantages of the degradability of such materials and the advantages of inorganic fillers in cost and material performance enhancement to develop degradable materials that are acceptable to the market. However, most of the traditional compatibilizers used for polymer material modification cannot be directly applied to the degradation system. Therefore, it is necessary to carry out research on compatibilization modification specifically for the degradation system. Summary of the invention
[0006] In view of this, the present invention aims to realize the preparation of high-performance and low-cost fully biodegradable composite polymer materials by using a fully biodegradable macromolecular compatibilizer. The invention can significantly improve the compatibility between polymers and many inorganic fillers, and the modified materials have good performance and can significantly reduce the material preparation cost.
[0007] The primary purpose of the present invention is to provide a fully biodegradable macromolecular compatibilizer.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned fully biodegradable macromolecular compatibilizer.
[0009] Another object of the present invention is to provide the application of the above-mentioned fully biodegradable macromolecular compatibilizer.
[0010] The object of the present invention is achieved by the following technical scheme: a fully biodegradable macromolecular compatibilizer, a carbon dioxide-based fully biodegradable polymer material composed of a carbonate bond and an ether bond structure segment as a hydrophilic end main chain and a siloxane-containing segment as a hydrophobic end side chain, and the structure is shown in formula (I):
[0011]
[0012] wherein R1 and R2 are independently selected from hydrogen, halogen, C1-22 aliphatic group, C1-22 substituted aliphatic group, C1-22 substituted heteroaliphatic group, aryl, substituted aryl or substituted heteroaryl;
[0013] R3 has the following structure:
[0014]
[0015] is a bridging group selected from a C1-12 alkyl chain, a C1-C16 alkyl chain or an alkenyl chain containing one or more ether, ester or carboxylic acid groups;
[0016] R4 is selected from hydrogen, halogen, C1-22 aliphatic, C1-22 substituted aliphatic, C1-22 substituted heteroaliphatic, aryl, substituted aryl or substituted heteroaryl;
[0017] Wherein m, n and p are integers between 5 and 1000 respectively.
[0018] The preparation method of the above-mentioned fully biodegradable macromolecular compatibilizer comprises the following steps:
[0019] Under anhydrous and oxygen-free conditions, a catalyst is weighed and added into a high-pressure reactor, and then a silicon-containing epoxy monomer and a third epoxy monomer are added into the reactor. After closing the reactor, carbon dioxide is introduced to carry out a polymerization reaction, and the fully biodegradable macromolecular compatibilizer is obtained by dissolving in dichloromethane and precipitating in ethanol or n-hexane.
[0020] Preferably, the catalyst is selected from at least one of a porphyrin aluminum complex / cocatalyst system, a porphyrin cobalt complex / quaternary ammonium salt system, a Schiff base cobalt complex / cocatalyst system, a zinc-cobalt double metal cyanide complex, a salicylaldehyde imine cobalt or chromium complex, a carboxylate zinc complex and a diimine zinc complex;
[0021] Preferably, the silicon-containing epoxy monomer is one or more of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, and 3-glycidyloxypropyltriethoxysilane.
[0022] Preferably, the third epoxy monomer is one or more of ethylene oxide, propylene oxide, 3-methylbutylene oxide, 1,2-epoxy-2-methylpropane, 1,2-butylene oxide, cyclohexene oxide, cyclopentane oxide, epichlorohydrin, or epoxidized animal and plant oils.
[0023] Preferably, the molar ratio of the silicon-containing epoxy monomer to the third epoxy monomer is 1:0.5-100;
[0024] Preferably, the molar ratio of the catalyst to the total amount of the silicon-containing epoxy monomer and the third epoxy monomer is 1:100 to 50000;
[0025] Preferably, the pressure of the carbon dioxide is 1 to 5 MPa, the temperature of the polymerization reaction is 20 to 90° C., and the time of the polymerization reaction is 1 to 12 hours.
[0026] The application of the fully biodegradable macromolecular compatibilizer can be used as a compatibilizer to prepare fully biodegradable composite polymer materials.
[0027] Preferably, the fully biodegradable composite polymer material is prepared by the following method:
[0028] Adding 1 to 10% by weight of a fully biodegradable macromolecular compatibilizer to calcium carbonate powder and mixing the mixture at 80° C. for 5 to 10 minutes using a high-speed mixer to obtain modified calcium carbonate powder;
[0029] Preferably, the particle size of the calcium carbonate powder is 100 to 500 mesh;
[0030] Weigh 5-50% by weight of modified calcium carbonate powder and mix it with biodegradable resin for 3-10 minutes, and after mixing, feed it into a twin-screw extruder for melting and plasticization, extrusion and granulation to obtain a fully biodegradable composite polymer material;
[0031] Preferably, the biodegradable resin is selected from one or more of polybutylene terephthalate adipate (PBAT), polybutylene adipate succinate (PBSA), polylactic acid (PLA), and carbon dioxide-based plastic (PPC).
[0032] Beneficial Effects
[0033] (1) The present invention provides a method for preparing a fully biodegradable macromolecular compatibilizer, which utilizes cheap and renewable carbon dioxide as a raw material and has excellent biodegradability compared to traditional small molecule compatibilizers.
[0034] (2) The present invention provides a method for modifying the blending of synthetic biodegradable polymer materials such as PBAT, PBSA, PLA, PPC and inorganic fillers using a fully biodegradable macromolecular compatibilizer, thereby solving the problem of poor compatibility between biodegradable polymer materials and inorganic fillers and the problem of poor compatibilization effect of traditional compatibilizers in the composite system of biodegradable polymer materials and inorganic fillers. The method can effectively reduce material costs and help promote application.
[0035] (3) Moreover, the improved compatibility of the synthetic biodegradable polymer material synthesized by the present invention after blending and modification with the expanded inorganic filler can be directly reflected in the significant improvement of the thermal and mechanical properties of the material. The tendency of the mechanical properties of the prepared polymer material blend to decrease with the increase of the filler feed ratio is weakened, and the performance is improved when the feed ratio is 5% to 40%, the tensile strength is increased by 10% to 50%, the elongation at break is increased by 1% to 5%, and the impact strength is increased by 40% to 100%.
[0036] (4) In addition, it should be noted that after adding the compatibilizer in the present invention, the mechanical properties of the material can still be effectively improved when the amount of inorganic filler added in the blend exceeds 40wt%. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the Fourier infrared transform spectrum of the fully biodegradable macromolecular compatibilizer X2 in Example 2.
[0038] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of the fully biodegradable macromolecular compatibilizer X2 in Example 2.
[0039] Figure 3 This is a scanning electron microscope image of the cross-section of the fully biodegradable composite polymer material in Example 12.
[0040] Figure 4 This is a scanning electron microscope image of the cross-section of the fully biodegradable composite polymer material in Comparative Example 3. DETAILED DESCRIPTION
[0041] The innovation of the present invention is to synthesize a fully biodegradable macromolecular compatibilizer, and use the compatibilizer to perform surface treatment on inorganic fillers. The compatibilizer can effectively improve the compatibility between inorganic fillers such as calcium carbonate and silicon dioxide and synthetic biodegradable polymer materials. When the amount of inorganic filler added exceeds 40wt%, the thermal and mechanical properties of the material can still be effectively improved, avoiding the uncertain factors such as cross-linking and precipitation of small molecular silane coupling agents during use. The main reason for the improvement of compatibility in the present invention is due to the special structure of the macromolecular compatibilizer, which contains a side chain of a siloxane structure and a polycarbonate segment, so it can effectively improve the compatibility between polycarbonates such as PPC and PBAT and polyester-type biodegradable polymers and inorganic fillers.
[0042] The present invention will be described in more detail below, wherein preferred embodiments of the present invention are listed, and it should be understood that those skilled in the art can modify the embodiments described herein and still achieve the beneficial effects of the present invention. Therefore, the following description should be understood as being widely known to those skilled in the art, and not as a limitation of the present invention.
[0043] For the sake of clarity, not all features of the actual embodiments are described. In the following description, well-known functions and structures are not described in detail because they would obscure the present invention with unnecessary details. It should be recognized that in the development of any actual embodiment, a large number of implementation details must be made to achieve the specific goals of the developer.
[0044] The inorganic filler used in the embodiment is treated by the following method: 500 g of inorganic filler and an appropriate amount of fully biodegradable macromolecular compatibilizer are added to a high-speed mixer, and mixed at 80° C. for 5 to 10 minutes to obtain modified calcium carbonate powder.
[0045] The raw materials used in other embodiments are all commercially available products unless otherwise specified, among which PBAT is purchased from BASF of Germany or Zhejiang Xinfu, and PLA is purchased from Zhejiang Hisun.
[0046] Example 1: Preparation of Compatibilizer X1
[0047] Prepare the components in the following proportions:
[0048]
[0049] After the autoclave is fully vacuum dried, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, propylene oxide, Schiff base cobalt complex (catalyst), and bistriphenylphosphorane ammonium chloride (co-catalyst) are added in proportion, and 3MPa of carbon dioxide is filled into the autoclave, and the reaction is carried out at 25°C for 8 hours. After the reaction is completed, excess carbon dioxide is released, and the polymer is dissolved with dichloromethane, washed with ethanol precipitation 3 times, and vacuum dried to obtain a fully biodegradable macromolecular compatibilizer X1. The contact angle test shows that the contact angle of the macromolecular compatibilizer is 87°, and the gel permeation chromatography (GPC) test (tetrahydrofuran as the mobile phase) shows that the number average molecular weight is 75500 and the molecular weight distribution is 1.22.
[0050] Example 2: Preparation of Compatibilizer X2
[0051] Prepare the components in the following proportions:
[0052]
[0053] After the autoclave is fully vacuum dried, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, propylene oxide, Schiff base cobalt complex (catalyst), and bistriphenylphosphorane ammonium chloride (cocatalyst) are added in proportion. After the autoclave is added, 3MPa carbon dioxide is filled into the autoclave and reacted at room temperature for 6 hours. After the reaction is completed, excess carbon dioxide is released and FTIR is used. 1 HNMR characterization of the structure of macromolecular compatibilizers, Figure 1 Medium 1750cm -1 The absorption peak of carbonyl group and Figure 2 The absorption peaks at 4.8-4.9ppm and 5.0ppm both prove the successful synthesis of the fully biodegradable macromolecular compatibilizer. The polymer was dissolved in dichloromethane, precipitated and washed with ethanol three times, and then dried in vacuo to obtain the fully biodegradable macromolecular compatibilizer X2. The contact angle test showed that the contact angle of the macromolecular compatibilizer was 107°, and the GPC test (tetrahydrofuran as the mobile phase) showed that the number average molecular weight was 93600 and the molecular weight distribution was 1.29.
[0054] Example 3: Preparation of Compatibilizer X3
[0055] Prepare the components in the following proportions:
[0056] 2-(3,4-Epoxycyclohexyl)ethyltrimethoxysilane 17 mL (74 mmol)
[0057] Propylene oxide 13mL (186mmo1)
[0058] Catalyst (heterogeneous) 8mg
[0059] After the autoclave is fully vacuum dried, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, propylene oxide, and zinc-cobalt double metal cyanide complex (catalyst) are added in proportion, and 3.5MPa of carbon dioxide is added to the autoclave, and the reaction is carried out at 80°C for 10 hours. After the reaction is completed, excess carbon dioxide is released, and the polymer is dissolved with dichloromethane, and the n-hexane precipitation is washed 3 times, and the fully biodegradable macromolecular compatibilizer X3 is obtained after vacuum drying. The contact angle test shows that the contact angle of the macromolecular compatibilizer is 100°, and the GPC test (tetrahydrofuran as the mobile phase) shows that the number average molecular weight is 5000 and the molecular weight distribution is 2.3.
[0060] Example 4: Preparation of Compatibilizer X4
[0061] Prepare the components in the following proportions:
[0062] 2-(3,4-Epoxycyclohexyl)ethyltrimethoxysilane 26 mL (113 mmol)
[0063] Propylene oxide 4mL (57mmol)
[0064] Catalyst (heterogeneous) 200mg
[0065] After the autoclave is fully vacuum dried, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, propylene oxide, and zinc glutarate (catalyst) are added in proportion, and 4.0MPa of carbon dioxide is added to the autoclave, and the reaction is carried out at 80°C for 12 hours. After the reaction is completed, excess carbon dioxide is released, and the polymer is dissolved with dichloromethane, washed with ethanol precipitation 3 times, and vacuum dried to obtain a fully biodegradable macromolecular compatibilizer X4. The contact angle test shows that the contact angle of the macromolecular compatibilizer is 105°, and the GPC test (tetrahydrofuran as the mobile phase) shows that the number average molecular weight is 110,000 and the molecular weight distribution is 1.9.
[0066] Example 5: Preparation of Compatibilizer X5
[0067] Prepare the components in the following proportions:
[0068]
[0069] After the autoclave is fully vacuum dried, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 1,2-epoxybutane, Schiff base cobalt complex (catalyst), bistriphenylphosphorane ammonium chloride (cocatalyst) are added in proportion, and 3.0MPa of carbon dioxide is added to the autoclave, and the reaction is carried out at 25°C for 8 hours. After the reaction is completed, excess carbon dioxide is released, and the polymer is dissolved with dichloromethane, washed with ethanol precipitation 3 times, and vacuum dried to obtain a fully biodegradable macromolecular compatibilizer X5. The contact angle test shows that the contact angle of the macromolecular compatibilizer is 80°, and the GPC test (tetrahydrofuran as the mobile phase) shows that the number average molecular weight is 75600 and the molecular weight distribution is 1.05.
[0070] Example 6: Preparation of Compatibilizer X6
[0071] Prepare the components in the following proportions:
[0072]
[0073] After the autoclave is fully vacuum dried, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, propylene oxide, Schiff base cobalt complex (catalyst), and bistriphenylphosphorane ammonium chloride (cocatalyst) are added in proportion, and 3.0MPa of carbon dioxide is added to the autoclave, and the reaction is carried out at 25°C for 6 hours. After the reaction is completed, excess carbon dioxide is released, and the polymer is dissolved with dichloromethane, washed with ethanol precipitation 3 times, and vacuum dried to obtain a fully biodegradable macromolecular compatibilizer X6. The contact angle test shows that the contact angle of the macromolecular compatibilizer is 103°, and the GPC test (tetrahydrofuran as the mobile phase) shows that the number average molecular weight is 68900 and the molecular weight distribution is 1.10.
[0074] Example 7: Preparation of fully biodegradable composite polymer material P1
[0075] Prepare the components in the following proportions:
[0076] PPC 100 copies
[0077] Macromolecular extender X1 0.2 parts
[0078] Calcium carbonate 20 parts
[0079] After sufficient vacuum drying, the PPC was added with the surface-modified calcium carbonate in the above proportion, mixed, added to a mixer and continued to be fully mixed for 10 minutes, and after mixing, fed into a twin-screw extruder for melt plasticization and extrusion granulation to obtain the fully biodegradable composite polymer material P1. The mechanical properties of the obtained material were tested according to GB / T 1040.3-2006, and the results showed that the tensile strength of the prepared blend was 29.3MPa and the elongation at break was 6.5%.
[0080] Example 8: Preparation of fully biodegradable composite polymer material P2
[0081] Prepare the components in the following proportions:
[0082] PPC 100 copies
[0083] Macromolecular extender X2 2 parts
[0084] Calcium carbonate 40 parts
[0085] After sufficient vacuum drying, the PPC was added with the surface-modified calcium carbonate in the above proportion, mixed, added to a mixer and continued to be fully mixed for 10 minutes, and after mixing, fed into a twin-screw extruder for melt plasticization and extrusion granulation to obtain the fully biodegradable composite polymer material P2. The mechanical properties of the obtained material were tested according to GB / T 1040.3-2006, and the results showed that the tensile strength of the prepared blend was 31MPa and the elongation at break was 4%.
[0086] Example 9: Preparation of fully biodegradable composite polymer material P3
[0087] Prepare the components in the following proportions:
[0088] PPC 100 copies
[0089] Macromolecular extender X3 0.5 parts
[0090] Calcium carbonate 50 parts
[0091] After sufficient vacuum drying, the PPC was added with the surface-modified calcium carbonate in the above proportion, mixed, added to a mixer and continued to be fully mixed for 10 minutes, and after mixing, fed into a twin-screw extruder for melt plasticization and extrusion granulation to obtain the fully biodegradable composite polymer material P3. The mechanical properties of the obtained material were tested according to GB / T 1040.3-2006, and the results showed that the tensile strength of the prepared blend was 20MPa and the elongation at break was 2%.
[0092] Example 10: Preparation of fully biodegradable composite polymer material P4
[0093] Prepare the components in the following proportions:
[0094] PPC 100 copies
[0095] Macromolecular extender X4 1 part
[0096] Calcium carbonate 10 parts
[0097] After sufficient vacuum drying, the PPC was added with the surface-modified calcium carbonate in the above proportion, mixed, added to a mixer and continued to be fully mixed for 10 minutes, and after mixing, fed into a twin-screw extruder for melt plasticization and extrusion granulation to obtain the fully biodegradable composite polymer material P4. The mechanical properties of the obtained material were tested according to GB / T 1040.3-2006, and the results showed that the tensile strength of the prepared blend was 26MPa and the elongation at break was 5.3%.
[0098] Example 11: Preparation of fully biodegradable composite polymer material P5
[0099] Prepare the components in the following proportions:
[0100] PPC 100 copies
[0101] Macromolecular compatibilizer X5 0.05 parts
[0102] 5 parts calcium carbonate
[0103] After sufficient vacuum drying, the PPC was added with the surface-modified calcium carbonate in the above proportion, mixed, added to a mixer and continued to be fully mixed for 10 minutes, and after mixing, fed into a twin-screw extruder for melt plasticization and extrusion granulation to obtain the fully biodegradable composite polymer material P5. The mechanical properties of the obtained material were tested according to GB / T 1040.3-2006, and the results showed that the tensile strength of the prepared blend was 25MPa and the elongation at break was 8.5%.
[0104] Example 12: Preparation of fully biodegradable composite polymer material P6
[0105] Prepare the components in the following proportions:
[0106] PPC 100 copies
[0107] Macromolecular extender X6 1.5 parts
[0108] Calcium carbonate 30 parts
[0109] After sufficient vacuum drying, the PPC was added with the surface-modified calcium carbonate in the above proportion, mixed, added to a mixer and continued to be fully mixed for 10 minutes, and after mixing, fed into a twin-screw extruder for melt plasticization and extrusion granulation to obtain the fully biodegradable composite polymer material P6. The mechanical properties of the obtained material were tested according to GB / T 1040.3-2006, and the results showed that the tensile strength of the prepared blend was 30MPa and the elongation at break was 7%.
[0110] Example 13: Preparation of fully biodegradable composite polymer material P7
[0111] Prepare the components in the following proportions:
[0112] PBAT 100 shares
[0113] Macromolecular extender X1 1 part
[0114] Calcium carbonate 20 parts
[0115] After sufficient vacuum drying, PBAT is added with the surface-modified calcium carbonate in the above proportion, mixed, added to a mixer and continued to be fully mixed for 10 minutes, and after mixing, fed into a twin-screw extruder for melt plasticization and extrusion granulation to obtain the fully biodegradable composite polymer material P7. The mechanical properties of the obtained material are tested according to GB / T 1040.3-2006. The results show that the tensile strength of the prepared blend is 52MPa and the elongation at break is 100%.
[0116] Example 14: Preparation of fully biodegradable composite polymer material P8
[0117] Prepare the components in the following proportions:
[0118] PBAT 100 shares
[0119] Macromolecular extender X2 2 parts
[0120] Calcium carbonate 40 parts
[0121] After PBAT is fully vacuum dried, the surface-modified calcium carbonate in the above proportion is added, mixed, added to a mixer and continued to be fully mixed for 10 minutes, and after mixing, fed into a twin-screw extruder for melt plasticization and extrusion granulation to obtain the fully biodegradable composite polymer material P8. The mechanical properties of the obtained material are tested according to GB / T 1040.3-2006. The results show that the tensile strength of the prepared blend is 60MPa and the elongation at break is 40%.
[0122] Comparative Example 1 (Comparative Example 8):
[0123] Prepare the components in the following proportions:
[0124] PPC 100 copies
[0125] Macromolecular extender X2 0 parts
[0126] Calcium carbonate 40 parts
[0127] The components are the same as those in Example 8, except that no macromolecular compatibilizer is added, and then the mechanical properties of the obtained material are tested according to GB / T1040.3-2006.
[0128] The results show that the tensile strength of the prepared blend is 22 MPa and the elongation at break is 3%.
[0129] Comparative Example 2 (Comparative Example 8):
[0130] Prepare the components in the following proportions:
[0131]
[0132] The same components as Example 8, the only difference is that the macromolecular compatibilizer is replaced by a small molecular silane coupling agent KH-560, and then the mechanical properties of the obtained material are tested according to GB / T 1040.3-2006.
[0133] The results show that the tensile strength of the prepared blend is 27MPa and the elongation at break is 3%.
[0134] Comparative Example 3 (Comparative Example 12):
[0135] Prepare the components in the following proportions:
[0136] PPC 100 copies
[0137] Macromolecular extender X6 0 parts
[0138] Calcium carbonate 30 parts
[0139] The same components as Example 12, except that no macromolecular compatibilizer was added, and then the mechanical properties of the obtained material were tested according to GB / T1040.3-2006.
[0140] The results show that the tensile strength of the prepared blend is 23MPa and the elongation at break is 3%. Figure 3 and Figure 4 The scanning electron microscope image for observing the morphological difference between Comparative Example 12 and Comparative Example 3 is shown. By comparison, it is found that after adding the macromolecular compatibilizer, the dispersion of calcium carbonate is more uniform and the agglomeration phenomenon is significantly weakened.
[0141] Comparative Example 4 (Comparative Example 14):
[0142] Prepare the components in the following proportions:
[0143] PBAT 100 shares
[0144] Macromolecular extender 0 parts
[0145] Calcium carbonate 40 parts
[0146] The components are the same as those in Example 14, except that no macromolecular compatibilizer is added, and then the mechanical properties of the obtained material are tested according to GB / T1040.3-2006.
[0147] The results show that the tensile strength of the prepared blend is 53 MPa and the elongation at break is 35%.
[0148] By comparing the examples and comparative examples, it can be shown that the tensile strength of the material without the large molecular compatibilizer is low, and the parameters such as the elongation at break are significantly reduced. It is fully proved that the fully biodegradable macromolecular compatibilizer of the present invention can effectively improve the compatibility of synthetic biodegradable polymer materials (such as carbon dioxide-based plastics (PPC), polybutylene adipate terephthalate (PBAT), polybutylene adipate succinate (PBSA), polylactic acid (PLA), etc.) with inorganic fillers such as calcium carbonate, improve mechanical properties, and avoid cross-linking and precipitation in the use of small molecular silane coupling agents disclosed in the prior art. Moreover, when the amount of calcium carbonate added exceeds 40wt%, the mechanical properties of the material can still be effectively improved.
[0149] The above describes the preferred embodiments of the present invention, but it is not intended to limit the present invention. Those skilled in the art may make improvements and changes to the embodiments disclosed herein without departing from the scope and spirit of the present invention.
Claims
1. An application of a fully biodegradable macromolecular compatibilizer, characterized in that: The fully biodegradable macromolecular compatibilizer is used as a compatibilizer to prepare a fully biodegradable composite polymer material; the fully biodegradable composite polymer material is prepared by the following method: 1 to 10% by weight of a fully biodegradable macromolecular compatibilizer is added to calcium carbonate powder, and mixed at 80° C. for 5 to 10 minutes using a high-speed mixer to obtain modified calcium carbonate powder; The particle size of the calcium carbonate powder is 100 to 500 meshes; Weigh 5-50% by weight of modified calcium carbonate powder and mix it with biodegradable resin for 3-10 minutes, and after mixing, feed it into a twin-screw extruder for melting and plasticization, extrusion and granulation to obtain a fully biodegradable composite polymer material; The fully biodegradable macromolecular compatibilizer is a carbon dioxide-based fully biodegradable polymer material composed of a carbonate bond and an ether bond structure segment as a hydrophilic end main chain and a siloxane segment as a hydrophobic end side chain, and the structure is shown in formula (I): wherein R1 and R2 are independently selected from hydrogen, halogen, C1-22 aliphatic group, C1-22 substituted aliphatic group, C1-22 substituted heteroaliphatic group, aryl, substituted aryl or substituted heteroaryl; R3 has the following structure: is a bridging group selected from a C1-12 alkyl chain, a C1-C16 alkyl chain or an alkenyl chain containing one or more ether, ester or carboxylic acid groups; R4 is selected from hydrogen, halogen, C1-22 aliphatic, C1-22 substituted aliphatic, C1-22 substituted heteroaliphatic, aryl, substituted aryl or substituted heteroaryl; Wherein m, n and p are integers between 5 and 1000 respectively.
2. The use of a fully biodegradable macromolecular compatibilizer according to claim 1, characterized in that: The preparation method of the fully biodegradable macromolecular compatibilizer comprises the following steps: under anhydrous and oxygen-free conditions, weighing a catalyst and adding it into a high-pressure reactor, then adding a silicon-containing epoxy monomer and a third epoxy monomer into the reactor, closing the reactor and injecting carbon dioxide to perform a polymerization reaction, dissolving it with dichloromethane, and precipitating it with ethanol or n-hexane to obtain the fully biodegradable macromolecular compatibilizer.
3. The use of a fully biodegradable macromolecular compatibilizer according to claim 2, characterized in that: The catalyst is selected from at least one of porphyrin aluminum complex / cocatalyst system, porphyrin cobalt complex / quaternary ammonium salt system, Schiff base cobalt complex / cocatalyst system, zinc-cobalt double metal cyanide complex, salicylaldehyde imine cobalt complex, carboxylic acid zinc complex and diimine zinc complex.
4. The use of a fully biodegradable macromolecular compatibilizer according to claim 2, characterized in that: The silicon-containing epoxy monomer is at least one of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane and 3-glycidyloxypropyltriethoxysilane.
5. The use of a fully biodegradable macromolecular compatibilizer according to claim 2, characterized in that: The third epoxy monomer is at least one of ethylene oxide, propylene oxide, 3-methylbutylene oxide, 1,2-epoxy-2-methylpropane, 1,2-butylene oxide, cyclohexene oxide, cyclopentane oxide, epichlorohydrin, or epoxidized animal and vegetable oils; The molar ratio of the silicon-containing epoxy monomer to the third epoxy monomer is 1:0.5-100; The molar ratio of the catalyst to the total amount of the silicon-containing epoxy monomer and the third epoxy monomer is 1:100 to 50000; The pressure of the carbon dioxide is 1-5 MPa, the temperature of the polymerization reaction is 20-90° C., and the time of the polymerization reaction is 1-12 hours.
6. The use of a fully biodegradable macromolecular compatibilizer according to claim 1, characterized in that: The biodegradable resin is selected from one or more of polybutylene terephthalate adipate PBAT, polybutylene adipate succinate PBSA, polylactic acid PLA, and carbon dioxide-based plastic PPC.
Citation Information
Patent Citations
Elastomer-containing silane coupling agent and preparation method thereof
CN112125927A
Process for improving thermal stability of aliphatic polycarbonate by organic silane
CN1306022A